2015
DOI: 10.3329/sja.v13i1.24183
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic components for plant growth and physiological traits of wheat (Triticum aestivum L) under normal and stress conditions

Abstract: This study was conducted to investigate the genetic variability of plant growth and physiological characters in thirty wheat genotypes under normal and drought stress conditions. Selection of important plant growth and physiological traits are essential component for wheat yield improvement. For this purpose, an experiment was conducted in the glasshouse during 2012-13 to estimate the extent of genetic components viz., genetic variance, coefficient of variability and broad sense heritability for plant growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…High broad sense heritability was observed for this trait, which indicated that selection would be effective (Table 2). Similar results were also discussed by Bayoumi et al (2008) and Naeem et al (2015).…”
Section: Cell Membrane Stabilitysupporting
confidence: 91%
“…High broad sense heritability was observed for this trait, which indicated that selection would be effective (Table 2). Similar results were also discussed by Bayoumi et al (2008) and Naeem et al (2015).…”
Section: Cell Membrane Stabilitysupporting
confidence: 91%
“…The highest PCV and GCV values were recorded for number of spikes per m 2 with values (95.12% and 73.61%; 140.34% and 111.12%) under normal and water stress irrigation, respectively. Followed by total chlorophyll, plant height and number of kernels/spikes which indicating the low effect of environment on the expression of these traits and the extent of PCV and GCV varied from one trait to another these results agree with Naeem et al, 2015.The results of broad-sense heritability (H 2 ) estimates show that there was gradation for all the traits studied with values ranging from 25% to 92% and 30% to 91% for normal irrigation and water stress treatment respectively. For normal irrigation, the highest value was 92% for grain weight/plot followed by flag leaf area, days to heading, 1000 kernel weight and plant height with values of 89%, 88%, 86% and 84%, respectively.…”
Section: Genetic Advance Parameterssupporting
confidence: 73%
“…Furthered, drought tolerance indices showed very high heritability indicating these indices affected by less environmental elements and selected easy because of high additive effect. Moreover, these superior heritability values were recorded in Table 4, indicated the possibility of improvement in the indices (Naeem et al, 2015;Besufikad, 2019 andSumanth et al, 2017). These results are partially constant with Darvishzadeh et al (2011) who demonstrated that MP, GMP, STI, HAM and YI have reasonable heritability and are capable to choose the genotypes with high yield in stress conditions.…”
Section: Broad Sense Heritability and Genetic Advancementioning
confidence: 88%
“…In some cases, GCV was near to PCV for Yp, Ys, TOL, SSI, GMP and HAM presenting the expression of these indices was influenced by genetic effects and they having potential to improve in further selection (Naeem et al, 2015). Since, PCV and GCV values greater than 20% are considered as high and values between 10% and 20% as medium, whereas values less than 10% are considered as low (Deshmukh et al, 1986).…”
Section: Phenotypic Genotypic Variances and Coefficient Of Variabilitymentioning
confidence: 99%
See 1 more Smart Citation